Digital Marketing Strategy For Market Visibility In Regulated B2b Services: A Case Study of A Hazardous Waste Transportation Firm In Indonesia - Andhana Aryo Wisesa, Enggal (Publisher Cv. Inara, 2026)
This paper will focus on how lack of digital marketing will limit the market presence and acquisition of clients in controlled business-to-business (B2B) service companies. Digital presence in the modern B2B procurement has ceased to be a discretion tool; instead, it is a legality-checking mechanism and supplier pre-screening tool at the initial stage. It is a single-case study with a qualitative design that seeks to examine PT Surya Cipta Wisesa, which is a hazardous waste transportation company in Indonesia that has low digital visibility, despite having good operational backgrounds. The information was gathered in the form of semi-structured interviews with internal participants and buyer-side informants, competitor digital audits, and document analysis. Results show that the major problem of the firm is not a lack of operations but a lack of legitimacy signalling: valuable resources cannot be seen when digitally mediated buyer screening occurs, which results in systematic non-consideration in sets of consideration. The internal evidence shows that the regulatory sensitivity and document management limitations- not cost is the major obstacle to the development of the digital presence. The paper proves that the way that digital marketing in controlled B2B settings works is as a legitimacy infrastructure, and not a promotional practice. It has proposed a gradual, legitimacy-first digital approach that is clearly defined in terms of definition of done and key performance indicators in each of the implementation phases. The study adds to the body of knowledge on B2B marketing by conceptualizing the digital absence as a strategic capability gap and provides useful recommendations on SMEs functioning in regulated markets of the emerging market.